2013
DOI: 10.1371/journal.pone.0080022
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid Receptor Type 2 as Mediator of Mesenchymal Stromal Cell Immunosuppressive Properties

Abstract: Mesenchymal stromal cells are non-hematopoietic, multipotent progenitor cells producing cytokines, chemokines, and extracellular matrix proteins that support hematopoietic stem cell survival and engraftment, influence immune effector cell development, maturation, and function, and inhibit alloreactive T-cell responses. The immunosuppressive properties of human mesenchymal stromal cells have attracted much attention from immunologists, stem cell biologists and clinicians.Recently, the presence of the endocannab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 36 publications
6
43
0
5
Order By: Relevance
“…Furthermore, the possible involvement of the cannabinoid system in MSC function was recently reported . In this study, the authors described the inversely correlated expression of the receptors for the cannabinoids CB1 and CB2 on cultured MSCs, with levels of the CB2 receptor increasing with the maturation of the cells, and showed that MSCs also contain detectable amounts of cannabinoids .…”
Section: Molecular Mechanisms Pathways and Mediators: Emerging Rolementioning
confidence: 74%
“…Furthermore, the possible involvement of the cannabinoid system in MSC function was recently reported . In this study, the authors described the inversely correlated expression of the receptors for the cannabinoids CB1 and CB2 on cultured MSCs, with levels of the CB2 receptor increasing with the maturation of the cells, and showed that MSCs also contain detectable amounts of cannabinoids .…”
Section: Molecular Mechanisms Pathways and Mediators: Emerging Rolementioning
confidence: 74%
“…This effect is likely to be due to the antioxidant effect, anti-inflammatory properties, or the beneficial effects of cannabis extract along with growth factors, and this effect is also confirmed by the MTT result. The function of cannabinoid receptors, CB (1) and CB (2), can also be considered as components of a new regulatory pathway for the involvement of a cannabinoid system in the stem cell viability (2,4,8,9,15,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…Upon CB2R activation, T cells undergo apoptosis and decreased proliferation in colitis. Additionally, activation of CB2R diminishes the recruitment of neutrophils, T cells and macrophages to the inflamed colon (Storr et al 2009;Singh et al 2012); reduces expression of adhesion molecules in brain endothelium, decreasing leukocyte engagement and recruitment (Ramirez et al 2012); attenuates monocytes adhesion to and migration across of primary human brain microvascular endothelial cells (Rom et al 2013); inhibits Th17 differentiation in experimental autoimmune encephalomyelitis (Kong et al 2014) and liver disease (Kong et al 2014;Guillot et al 2014); inhibits the production of proinflammatory cytokines (IL-1␤, IL-6, IL-8, TNF␣ and IL-17) in splenocytes (Gui et al 2013), in human mesenchymal stromal cells (Rossi et al 2013), and in iris and ciliary body tissue (Toguri et al 2014). Furthermore, activation of CB2R reduces neovascularization in a model of sponge-induced inflammatory angiogenesis (Guabiraba et al 2013), which might be helpful to suppress synovial angiogenesis and pannus formation in RA.…”
Section: Discussionmentioning
confidence: 99%